Effects of domestic processing methods on the phytochemical content of watercress (Nasturtium officinale). (1st December 2016) - Giallourou, Natasa; Oruna-Concha, Maria Jose; Harbourne, Niamh
Highlights: This is the first report on the effects of processing on watercress phytochemicals. Negative correlation between boiling of watercress and phytochemical levels. Microwaving and steaming ensure better retention of all phytochemicals measured. Abstract: The impact of conventional cooking and processing methods on total phenols, antioxidant activity, carotenoids and glucosinolates of watercress was evaluated. Boiling significantly decreases phenolic content, antioxidant activity and recoverable glucosinolates, however it increases the carotenoid concentrations of watercress as compared to the raw vegetable. Cooking by microwaving and steaming maintains the majority of phytochemicals in comparison to the fresh material, suggesting that they should be used as the preferred methods of watercress preparation. Boiling of watercress should be avoided to ensure maximum ingestion of watercress-derived beneficial phytochemicals.